Value of serum soluble syndecan- 1 as a biomarker of disease activity in ulcerative colitis patients - Fatma M. Abdelsalam; Walid Abdellatif Abdelhalim; Ahmed M. Saleh; Tamer E. Eleraky (Egyptian Liver Journal)
Abstract Background Inflammatory bowel disease (IBD) is a chronic and incurable disease that includes Crohn’s disease (CD) and ulcerative colitis (UC); UC is characterized by repeated episodes of relapse and remission despite treatment; Soluble syndecan-1(Sdc1) is a marker of activity for UC. This study aimed to identify the role of Sdc1 in assessment of disease activity in UC. Methods Seventy-five consecutive patients with UC were included in this cross-sectional case–control study. Patients were stratified into two groups: group I (patients with UC) and then subdivided into group IA (patients with active disease), group IB (patients with inactive disease); and Group II (healthy controls). Detailed history, clinical examination, routine laboratory investigations, and full colonoscopy with biopsy were performed. Colonoscopic and histopathological findings were analyzed to determine the presence of organic diseases. Results Serum Sdc1 levels were significantly higher in active UC (7.60 ± 1.85 ng/mL) compared to inactive UC (4.48 ± 1.55 ng/mL) and controls (2.69 ± 1.09 ng/mL) (p < 0.001). Sdc1 levels correlated positively with bowel movement frequency, fecal calprotectin, ESR, and C-reactive protein (CRP), while negatively correlating with albumin (p < 0.05). Analysis showed that Sdc1 levels > 5.61 ng/mL distinguished active from inactive UC with 84% sensitivity and 76% specificity (AUC = 0.898, p < 0.001). Conclusions Sdc1 is a valuable biomarker for assessing disease activity in UC patients that shows strong correlations with clinical indicators and endoscopic findings.